HISTORICAL AND MUSICAL PARALLELS IN TRADITIONAL MUSIC OF AZERBAIJAN AND ALTAI (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the author examines historical and musical parallels in the traditional music of Azerbaijan and Altai. The article is relevant for researchers studying the musical culture of the Turkic peoples.
Keywords: Musical art of Azerbaijan, musical art of Altai, rhythmic mugams, meykhana